An analytical method for the optical analysis of Linear Fresnel Reflectors with a flat receiver. (October 2021) - Santos, Andre Vitor; Canavarro, Diogo; Horta, Pedro; Collares-Pereira, Manuel
Highlights: An analytical optical method for Linear Fresnel Reflectors with a flat receiver is presented. Analytical results agree very well with ray tracing for both factorized and biaxial models. Higher errors are seen for high incidence angles, especially for the longitudinal incidence. Intercept factor errors can be high up to 132%, although energetic differences can be high up to 3%. Abstract: The optical analysis of Linear Fresnel Reflectors solar concentrators deals with the calculation of the absorbed flux at the receiver. Due to concentrator discrete and complex geometry ray tracing numerical simulations is the main used method, in parallel with some analytical approaches that have been developed for specific cases. This paper presents an analytical method for Linear Fresnel Reflectors with a flat receiver. It is based on Zhu's vector-based method and Rabl's concepts of acceptance and effective source, although new shading (including receiver shading), blocking, and cosine losses analyzes are presented, with the inclusion of end-losses effect. As shown, the problem is better described by the concept of intercept factor, the effective aperture area used to collect the incident sunlight. Comparison tests with ray tracing simulations performed in SolTrace for three different effective sources were carried out to validate the analytical model for both factorized and biaxial models of the intercept factor, including energetic evaluations for Évora, Portugal. In general, analytical results do agree very well with ray tracing, better for the factorized model than the biaxial. Errors in the analytical estimative of intercept factor can be high up to 132% for the biaxial model at high longitudinal incidence angles; on the other hand, errors in the amount of annual absorbed energy were high up to only 3%.